2005
DOI: 10.1055/s-2005-865098
|View full text |Cite
|
Sign up to set email alerts
|

S3-Guidelines Colorectal Cancer 2004

Abstract: Klassifikation der Konsensusstärke starker Konsens Zustimmung von > 95 % der Teilnehmer Konsens Zustimmung von > 75 -90 % der Teilnehmer mehrheitliche Zustimmung Zustimmung von > 50 -75 % der Teilnehmer kein Konsens Zustimmung von < 50 % der Teilnehmer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
32

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 218 publications
(284 reference statements)
1
43
0
32
Order By: Relevance
“…These results may therefore have important implications for the offer of CRC screening programmes and their optimisation in terms of cost effectiveness. The choice of different, risk adapted ages at initiation of screening is well accepted and established for CRC risk factors other than gender, in particular a history of CRC before age 60 in a first degree relative (Winawer et al, 2003;Schmiegel et al, 2004;Smith et al, 2006). Although the relative risk of CRC among people with such a family history compared to those without is larger than the relative risk of men compared to women (Johns and Houlston, 2001), the prevalence of the former risk factor in the population is much lower than the 'prevalence' of male gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may therefore have important implications for the offer of CRC screening programmes and their optimisation in terms of cost effectiveness. The choice of different, risk adapted ages at initiation of screening is well accepted and established for CRC risk factors other than gender, in particular a history of CRC before age 60 in a first degree relative (Winawer et al, 2003;Schmiegel et al, 2004;Smith et al, 2006). Although the relative risk of CRC among people with such a family history compared to those without is larger than the relative risk of men compared to women (Johns and Houlston, 2001), the prevalence of the former risk factor in the population is much lower than the 'prevalence' of male gender.…”
Section: Discussionmentioning
confidence: 99%
“…Various screening examinations, including faecal occult blood testing (FOBT), sigmoidoscopy, and colonoscopy have meanwhile been recommended by expert committees and implemented in screening offers in a number of countries (e.g. Winawer et al, 2003;Schmiegel et al, 2004;Malila et al, 2005;Smith et al, 2006). Regarding the age at initiation of screening, which is a crucial parameter for the effectiveness and cost-effectiveness of screening programmes (Vijan et al, 2001), there is some variation between countries (typically ranging from 50 to 60 years for the population at average risk).…”
mentioning
confidence: 99%
“…[548], ein systematisches Review [553], eine prospektive Fallkontrollstudie [549] und eine retrospektive Fallserie [551] identifiziert, die in die Bewertung ebenfalls mit eingegangen sind (Einzelheiten siehe Evidenzbericht). Die bisherige Empfehlung mit einem Grad B für die PET/PET-CT-Untersuchung vor einer Resektion von kolorektalen Lebermetastasen bei einem FONG-Score > 2 der letzten Leitlinienaktualisierung 2008 wurde geändert, da die Studie, die zu dieser Empfehlung führte, bis heute nicht als Vollmanuskript publiziert ist [840]. Zur Frage des Patienten-relevanten Nutzens der PET/PET-CT ist bislang eine RCT als Vollpublikation und 1 RCT in Abstraktform publiziert.…”
Section: Hintergrundunclassified
“…Single agent panitumumab is currently recommended for use in second or subsequent lines of therapy, as an alternative to single agent cetuximab. 1,2 Several clinical trials have demonstrated that EGFR-targeted therapies are not effective in patients whose tumors have a mutation in the oncogene Kirsten ras (KRAS). [3][4][5][6][7][8][9][10][11] Tumors that have a mutation in codon 12 or 13 of the KRAS gene will not respond to treatment with EGFR inhibitors such as cetuximab or panitumumab.…”
Section: Introductionmentioning
confidence: 99%
“…4,10,11 Current U.S. and European guidelines recommend that all mCRC patients receive tumor KRAS testing before consideration of treatment with an EGFR inhibitor and state that patients with known KRAS mutations should not receive either cetuximab or panitumumab as there is very little chance of a clinical benefit and the exposure to toxicity and highcost of treatment cannot be justified. 1,2 Although some studies have examined the cost-effectiveness of cetuximab treatment, [12][13][14][15] limited data exist on the cost-effectiveness or the potential cost savings that might accrue from the use of KRAS testing. Our objective was to determine the cost-effectiveness of testing for KRAS mutations before administering cetuximab or panitumumab for patients with mCRC in the United States and Germany and to document the economic implications of KRAS testing.…”
Section: Introductionmentioning
confidence: 99%